2019
DOI: 10.1016/j.cageo.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

IGUG: A MATLAB package for 3D inversion of gravity data using graph theory

Abstract: We present an open source MATLAB package, IGUG, for 3D inversion of gravity data. The algorithm implemented in this package is based on methodology that was introduced by Bijani et al. (2015). A homogeneous subsurface body is modeled by an ensemble of simple point masses. The model parameters are the Cartesian coordinates of the point masses and their total mass. The set of point masses is associated to the vertices of a weighted full graph in which the weights are computed by the Euclidean pairwise distances … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…According to the studies shown in [10,15,56,57], the objective function for gravity inversion is comprised of data misfit and model misfit. By introducing regularization factor λ, the objective function is written as:…”
Section: Gravity Inversion With Multiplicative Regularization 231 Inv...mentioning
confidence: 99%
“…According to the studies shown in [10,15,56,57], the objective function for gravity inversion is comprised of data misfit and model misfit. By introducing regularization factor λ, the objective function is written as:…”
Section: Gravity Inversion With Multiplicative Regularization 231 Inv...mentioning
confidence: 99%
“…The same observed gravity data can be obtained by different sub-surface density distributions (Blakely, 1996;Rezaie et al, 2017). Therefore, many effective methods with addition constraint on density model are studied to obtain a reasonable and accuracy solution (Boulanger and Chouteau, 2001;Silva and Barbosa, 2006;Commer, 2011;Vatankhah et al, 2017;Vatankhah et al, 2018;Vatankhah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%